2012
DOI: 10.1021/jp306626y
|View full text |Cite
|
Sign up to set email alerts
|

Proton Conducting Ionic Liquid Doped Nafion Membranes: Nano-Structuration, Transport Properties and Water Sorption

Abstract: The impact of triethylammmonium trifluorosulfonate (TFTEA) concentration on the nanostructuration and electrochemical, thermo mechanical, transport properties of doped Nafion membranes has been studied. The Nafion membranes neutralized with triethylamine (Nafion–TEA) have been doped with various amounts of TFTEA using the swelling method. The effect of the TEA neutralization was first studied. The results suggest a specific arrangement of TEA cations and a quite low water uptake. Concerning TFTEA doped membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 50 publications
8
83
0
Order By: Relevance
“…22 We also note that our approach naturally provides all ingredients for generating a virtually infinite range of composite materials, obtained by doping the ionomer with elongated charged macro-molecules, including ionic liquids 23,24 .…”
Section: Discussionmentioning
confidence: 98%
“…22 We also note that our approach naturally provides all ingredients for generating a virtually infinite range of composite materials, obtained by doping the ionomer with elongated charged macro-molecules, including ionic liquids 23,24 .…”
Section: Discussionmentioning
confidence: 98%
“…However, at concentrations higher than 20 wt%, the resulting membranes were whitish opaque in appearance and also suffered from eventual exudation of the PCIL [10]. In the case of C4 and C8 doped membranes, the maximal PCIL concentrations were much higher, 40 wt% and 50 wt% for C4 and C8 respectively.…”
Section: A Thermal Propertiesmentioning
confidence: 99%
“…In our previous papers, we investigated the impact of morphology and method of elaboration on the functional properties of the PEMs based on Nafion ® + Triethylammonium trifluoromethane sulfonate (C1). We observed that the nanostructuration of Nafion ® membrane remains intact after the addition of C1 molecules even at high PCIL concentrations (up to 29 wt%) and casting, as a method of elaboration, provides better thermo-mechanical stability as well as lower gas permeability to the doped membranes [10,18]. Furthermore, use of well-chosen PCILs could also be beneficial for the Oxygen Reduction Reaction (ORR) activity of the platinum catalyst on the electrode.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations